The fitness-fatigue model: what`s in the numbers? - Vermeire, K.; Ghijs, M.; Bourgois, J. G.; Boone, J. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The purpose of this commentary is to outline some of the pitfalls when using the fitness-fatigue model to unravel the interaction between training load and performance. By doing so, we encourage sport scientists and coaches to interpret the parameters from the model with some extra caution.